Risk factors for sporadic Shiga toxin-producing Escherichia coli O157 infections in FoodNet sites, 1999–2000 - VOETSCH, A. C. (Cambridge University Press, 2007)
To monitor risk factors for illness, we conducted a case-control study of sporadic Shiga toxin-producing Escherichia coli O157 (STEC O157) infections in 1999–2000. Laboratory-confirmed cases of STEC O157 infection were identified through active laboratory surveillance in all or part of seven states. Patients and age-matched controls were interviewed by telephone using a standard questionnaire. Information was collected on demographics, clinical illness, and exposures to food, water, and animals in the 7 days before the patient's illness onset. During the 12-month study, 283 patients and 534 controls were enrolled. STEC O157 infection was associated with eating pink hamburgers, drinking untreated surface water, and contact with cattle. Eating produce was inversely associated with infection. Direct or indirect contact with cattle waste continues to be a leading identified source of sporadic STEC O157 infections.